2013
DOI: 10.1161/circulationaha.113.001278
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the CCR5 Antagonist Maraviroc in Reducing Early, Ritonavir-Induced Atherogenesis and Advanced Plaque Progression in Mice

Abstract: Background-CCR5 plays an important role in atherosclerosis and ischemic cardiovascular diseases, as well as in HIV replication and diffusion. HIV infection is characterized by a high burden of cardiovascular diseases, particularly in subjects exposed to ritonavir-boosted protease inhibitors. Maraviroc, a CCR5 antagonist antiretroviral drug, might provide benefit for patients with M-tropic HIV infections at high risk for cardiovascular diseases. Methods and Results-Exposure to maraviroc limits the evolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 45 publications
3
98
0
1
Order By: Relevance
“…HIV CCR5 co-receptor, which plays a crucial role in HIV viral entry, is also involved in many inflammatory pathways (1)(2)(3)(4)(5). MVC is the only available CCR5 antagonist currently used in clinical practice for treating HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV CCR5 co-receptor, which plays a crucial role in HIV viral entry, is also involved in many inflammatory pathways (1)(2)(3)(4)(5). MVC is the only available CCR5 antagonist currently used in clinical practice for treating HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 expression on monocytes/macrophage and T-cells and both endothelial and vascular smooth muscle cells suggests a key role in the atherosclerotic process. Several studies demonstrated that inhibition of this co-receptor produces an anti-inflammatory and anti-atherogenic effect (1)(2)(3)(4)(5). A body of evidence has documented that in patients with HIV, atherosclerosis is accelerated and chronic inflammatory processes are activated (6)(7)(8)(9); furthermore, certain evidence indicates that hepatitis C (HCV) co-infection can augment the risk of cardiovascular events (10,11).…”
mentioning
confidence: 99%
“…IL-1β increases dynamically following CME and is associated with impaired cardiac function [37] . RANTES has been identified as a specific marker for unstable angina pectoris by several studies [38][39] . The adhesion molecule, ICAM-1, also represents a marker of slow coronary flow caused by microvascular dysfunction [40][41] .…”
Section: Wwwchinapharcom Zhang Y Et Almentioning
confidence: 99%
“…So, there are good evidences that linked CCR5 to liver diseases (e.g., hepatocellular carcinoma and liver steatosis), [3][4][5][6] autoimmune disorders (e.g., rheumatoid arthritis), [7] pulmonary diseases (e.g., pulmonary arterial hypertension and sarcoidosis), [8,9] organ rejection (e.g., stem cell transplant), [10] malignancies (e.g., colorectal cancer), [11] and vascular diseases (e.g., endothelial dysfunction and atherogenesis). [12,13] Therefore, we wonder if CCR5 antagonist could be an attractive therapeutic option to prevent and/or treat different inflammatory and/or malignant diseases. Indeed, the absence of functional CCR5 is well tolerated in humans homozygous for the CCR5Δ32 mutation.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%
“…In this regard, interesting data have been obtained with MVC from studies using murine models designed to prevent liver cancer [5] or nonalcoholic fatty liver disease, [6] or treating atherogenesis, [13] or pulmonary arterial hypertension, [9] were also very relevant because this drug was effective preventing the rejection. [22] Nonetheless, not always the use of MVC supports its use as a therapeutic strategy.…”
Section: Off-label Use Of Maraviroc In Clinical Practicementioning
confidence: 99%